Koncentracija radona v prezračevanih notranjih prostorih v Hong Kongu - Lin, Zhang (Strojniški vestnik, 2000)
The radon emanation rate has been found to be much higher for building materials from Hong Kong compared with those from other places. Exposure to high radon levels poses a serious health risk. For the purpose of carrying out a worst-case analysis of the indoor radon concentration it was assumed that no finishing materials are applied to the floor, walls and ceiling. The level of indoor radon radiation in the air is studied by hand calculation and Computational Fluid Dynamics simulation using different air exchange rates to evaluate the influence of ventilation rate on the indoor-air radon level. Results show that the ventilation rate plays a very important role in controlling the indoor radon concentration. It is concluded that radon in offices is, in general, not a major factor when considering ventilation rate, although it is always advisable to keep the radon level as low as practically possible.
Keywords: prezračevanje prostorov; koncentracije radona; materiali gradbeni; analize; radon; bivalno okolje; prezračevanje